2020
DOI: 10.1111/apt.15969
|View full text |Cite
|
Sign up to set email alerts
|

Faecal immunochemical testing for adults with symptoms of colorectal cancer attending English primary care: a retrospective cohort study of 14 487 consecutive test requests

Abstract: Summary Background Faecal immunochemical testing (FIT) is recommended by the National Institute for Health and Care Excellence (NICE) to triage symptomatic primary care patients for further investigation of colorectal cancer. Aim To ascertain the diagnostic performance of FIT in symptomatic adult primary care patients. Methods Faecal samples from routine primary care practice in Oxfordshire, UK were analysed using the HM‐JACKarc FIT method between March 2017 and March 2020. Clinical details were recorded. Pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 34 publications
(59 reference statements)
4
69
2
Order By: Relevance
“…In symptomatic patients, a primary care study in the UK reported a sensitivity and specificity of 91% for CRC for a FIT result ≥10 μg/g (ref. 39 ). In this respect, FIT can be considered as the first quantitative laboratory biomarker in use for CRC risk stratification.…”
Section: Current Risk Stratificationmentioning
confidence: 99%
“…In symptomatic patients, a primary care study in the UK reported a sensitivity and specificity of 91% for CRC for a FIT result ≥10 μg/g (ref. 39 ). In this respect, FIT can be considered as the first quantitative laboratory biomarker in use for CRC risk stratification.…”
Section: Current Risk Stratificationmentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article. 4 Brian Shine 4…”
Section: Ack N Owled G Em Entmentioning
confidence: 99%
“…We presented evidence from a symptomatic cohort, tested in primary care in the context of NICE DG30 guidance. 4 Turvill rightly cautions against extrapolating estimates of risk associated with positive or negative test results from one population to another with a different disease prevalence. He illustrates this by comparing our 'lowrisk' symptomatic primary care population (DG30) with the 'high-risk' symptomatic referred population (NG12).…”
mentioning
confidence: 99%
“…Perhaps because of this, there was relatively little co‐ordinated data collection for patient outcomes when FIT was introduced in this setting. The excellent paper by Nicholson et al is, therefore, extremely welcome 1 . Because of its high specificity, FIT has proven effective in identifying over 90% of patients with colorectal cancer among a cohort of people who would not ordinarily be referred with suspected colorectal cancer, without generating large numbers of unnecessary additional colonoscopies.…”
mentioning
confidence: 99%